PENGARUH PERTUMBUHAN PENJUALAN, INTENSITAS ASET TETAP, INTENSITAS MODAL, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) - Rahmah, Ridhan (Restitusi : Jurnal Riset Perpajakan, 2023)
This research was conducted to determine and analyze sales growth, fixed asset intensity, capital intensity, leverage and profitability on tax avoidance. The sample used in this study was 79 companies originating from manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The data analysis technique used is multiple linear regression analysis using the SPSS program. The results of this study indicate that fixed asset intensity, capital intensity, leverage, profitability have a positive and significant effect on tax avoidance, while sales growth has a negative effect on tax avoidance.